Mamon di Meja Perjamuan: Kritik Profetik Terhadap Ketamakan Religius dan Ekonomi yang Menyingkirkan Orang Miskin - Benediktus James Widya Darmaka; Andreas Andry Handiyanto; Agus Suhariono (Jurnal EFATA: Jurnal Teologi dan Pelayanan, 2026)
Religious and economic greed constitute a theological problem that cannot be reduced to individual moral weakness. Through a qualitative approach employing theological construction and prophetic anti-mammonic critique, mammon is read as a power that displaces the loyalty of faith, shapes human imagination toward material possessions, and structures social relations according to accumulation, status, and economic honor. The metaphor of the banquet table is employed to expose the ecclesial irony whereby a space meant to declare grace, equality, and the body of Christ can instead be captured by a class logic that excludes the poor. The findings demonstrate that greed becomes most dangerous when sacralized through the language of blessing, abundance, success, and growth, for such language can conceal exploitation, silence the experience of the poor, and blunt the church's prophetic critique. The church must be formed as an anti-mammonic community, that is, a community that refuses to make wealth the measure of human dignity, restores the voice of the poor, theologically examines its fellowship practices, and makes the table of Christ a praxis of justice. Thus, the critique of greed is not merely a call to generosity but a summons to dismantle religious-economic structures that continue to exclude the poor from the center of the church's life. Abstrak Ketamakan religius dan ekonomi merupakan persoalan teologis yang tidak dapat direduksi menjadi kelemahan moral individu. Melalui pendekatan kualitatif dengan konstruksi teologis dan kritik profetik anti-mamonik, mamon dibaca sebagai kuasa yang menggeser loyalitas iman, membentuk imaji-nasi manusia terhadap harta, serta menata relasi sosial berdasarkan akumulasi, status, dan kehormatan ekonomi. Metafora meja perjamuan digunakan untuk menyingkap ironi gerejawi ketika ruang yang seharusnya menyatakan anugerah, kesetaraan, dan tubuh Kristus justru dapat direbut oleh logika kelas yang menyingkirkan orang miskin. Hasil pembahasan menunjukkan bahwa ketamakan menjadi paling berbahaya ketika disakralkan melalui bahasa berkat, kelimpahan, keberhasilan, dan pertumbuhan, sebab bahasa tersebut dapat menyembunyikan eksploitasi, membungkam pengalaman orang miskin, dan menumpulkan kritik profetik di dalam gereja. Gereja perlu dibentuk sebagai komunitas anti-mamonik, yaitu komunitas yang menolak menjadikan harta sebagai ukuran martabat, memulihkan suara orang miskin, menguji praktik persekutuan secara teologis, serta menjadikan meja Kristus sebagai praksis keadilan. Dengan demikian, kritik terhadap ketamakan bukan sekadar seruan kemurahan hati, melainkan panggilan untuk membongkar struktur religius-ekonomi yang membuat orang miskin tetap tersingkirkan dari pusat kehidupan gereja.